2016
DOI: 10.1021/acs.jpcc.6b04264
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Polysulfide Radical Anions in Ether-Based Solvents

Abstract: Lithium sulfur batteries have a theoretical specific energy 5 times greater than current lithium ion battery standards, but suffer from the issue of lithium polysulfide dissolution. The reaction mechanisms that underlie the formation of lithium polysulfide reaction intermediates have been studied for over four decades, yet still elude researchers. Polysulfide radical anions formed during the redox processes have become a focal point of fundamental Li−S battery research. The formation of radical species has eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 47 publications
(98 reference statements)
6
59
0
Order By: Relevance
“…Considering that the formed radical species are usually favorable for the electrochemical pathways. Wujcik et al examined the presence of radical polysulfide species in ether‐based solvents (tetraethylene glycol dimethyl ether and poly(ethylene oxide)) via a combination of EPR and ultraviolet–visible (UV–Vis) spectroscopy (Figure c,d) . EPR and UV–Vis results verified the presence of radical species in ether‐based electrolytes.…”
Section: Advanced Characterization and Mechanism Research In Li–s Batmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering that the formed radical species are usually favorable for the electrochemical pathways. Wujcik et al examined the presence of radical polysulfide species in ether‐based solvents (tetraethylene glycol dimethyl ether and poly(ethylene oxide)) via a combination of EPR and ultraviolet–visible (UV–Vis) spectroscopy (Figure c,d) . EPR and UV–Vis results verified the presence of radical species in ether‐based electrolytes.…”
Section: Advanced Characterization and Mechanism Research In Li–s Batmentioning
confidence: 98%
“…c) EPR spectra obtained for tetraethylene glycol dimethyl ether (TEGDME) and poly(ethylene oxide) (PEO) lithium polysulfide solutions for x mix values of 6. d) UV–vis spectra obtained for TEGDME and PEO lithium polysulfide solutions at sulfur concentrations of 10 × 10 −3 m . Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Advanced Characterization and Mechanism Research In Li–s Batmentioning
confidence: 99%
“…Impedance spectroscopy has also been used to evaluate the individual contributions from electrolyte resistance, charge transfer, ion diffusion and electrode surface layers, which in turn has been used to refine mechanistic models of Li−S cells,, as well as to investigate capacity fading . Other experimental techniques used to elucidate redox and diffusion properties in Li−S cells include XAS, in‐operando optical imaging of the temporal and spatial distribution of polysulfides, UV‐Vis spectroscopy, NMR, EPR/ESR,, XRD, Raman, HPLC, and gas evolution, among other electrochemical studies . The mechanism and kinetics of Li 2 S precipitation has been studied using chronoamperometry .…”
Section: Introductionmentioning
confidence: 99%
“…PEO can possibly promote the formation of lithium polysulfide radicals, as found in Ref. 28. The authors showed, by ab-initio simulation, that the -C=O groups in PVP exhibit high binding energies of 1.14 and 1.30 eV with Li 2 S and PS radical species.…”
Section: Resultsmentioning
confidence: 73%